Pengaruh Kualitas Produk, Kualitas Pelayanan dan Promosi Terhadap Kepuasan Pelanggan di Kopi Kenangan Plaza Kalibata - may siska puspita sari; Salman Paludi (Panorama Nusantara, 2022)
The purpose of this study was to determine the effect of product quality, service quality and promotion on customer satisfaction at Kopi Kenangan Plaza Kalibata. The population in this study were buyers who made purchases from April 2022 to July 2022. The sampling technique used purposive sampling to determine 100 respondents. Data collection using purposive sampling technique using a questionnaire that has been tested for validity and reliability. Descriptive and quantitative data analysis methods. Quantitative analysis using IBM SPSS Statistics 20 with Multiple Linear Regression method. The results showed that product quality had a significant effect on customer satisfaction with a t-statistic value of 10,5% and Service quality has a significant effect on customer satisfaction with a t-statistic value of 8.3% while the effect of promotion on customer satisfaction has a significant effect with a t-statistic value of only 1.4%.